ANALYSIS OF ASSESSING THE EFFICIENCY OF FOREIGN INVESTMENTS IN THE EXAMPLE OF DEVELOPED AND DEVELOPING COUNTRIES - Rozali Ashiraliyev (Modern American Journals, 2025)
This study examines the practices of assessing the efficiency of foreign investments in the example of Germany, South Korea, India and Turkey. The study analyzes how foreign direct investments (FDI) affect the economies of countries, in particular industrial development, inflation rate and foreign trade. Through graphical analysis, the relationships between FDI growth rates, changes in the inflation rate and the share of industry in GDP were studied, and specific conclusions were drawn for each country. The results of the study show that the efficiency of FDI is closely related not only to economic factors, but also to political stability, institutional environment and the level of technological development. In addition, high or low inflation directly affects FDI flows. The share of industry in GDP is considered one of the important indicators of investment attractiveness.
Keywords: Foreign investment, FDI, inflation, industry share, Germany, South Korea, India, Turkey, investment climate, economic stability, foreign trade.